2005
DOI: 10.1002/clc.4960280409
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 receptor antagonist levels correlate with extent of myocardial loss in patients with acute myocardial infarction

Abstract: SummaryBackground: Interleukin-1 receptor antagonist (IL-1Ra) levels are elevated early in patients with acute myocardial infarction (MI) and often precede release of markers of necrosis; however, IL-1Ra levels did not correlate previously with infarct size and prognosis in such patients.Hypothesis: The goal of our study was to evaluate prospectively the correlation between IL-1Ra levels upon emergency department (ED) presentation and the extent of myocardial necrosis and prognosis in patients with ST-segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…7 Its levels are elevated early in patients presenting with ST-segment-elevation AMI, 5 and the greater the area of myocardium at risk is, the greater the increase in IL-1Ra levels is. 6 Moreover, in observational studies, higher IL-1Ra levels in patients with acute coronary syndromes were associated with unfavorable outcome. 20,21 Whether IL-1Ra represented a marker of damage, an attempt at cardioprotection by means of antiinflammatory activity, or a mediator of damage remained unclear.…”
Section: Il-1ra In Amimentioning
confidence: 99%
See 1 more Smart Citation
“…7 Its levels are elevated early in patients presenting with ST-segment-elevation AMI, 5 and the greater the area of myocardium at risk is, the greater the increase in IL-1Ra levels is. 6 Moreover, in observational studies, higher IL-1Ra levels in patients with acute coronary syndromes were associated with unfavorable outcome. 20,21 Whether IL-1Ra represented a marker of damage, an attempt at cardioprotection by means of antiinflammatory activity, or a mediator of damage remained unclear.…”
Section: Il-1ra In Amimentioning
confidence: 99%
“…3,4 Like other acute-phase reactants, IL-1Ra levels increase during AMI, and its levels correlate with prognosis. 5,6 The role of increasing IL-1Ra during AMI is unclear, and speculations have been made that its role ranges from merely a marker of damage to a modulator of the inflammatory response to a potential cytoprotective agent. 5,8 Recently, forced expression of IL-1Ra in an animal model has been shown to be cardioprotective in terms of reduced infarct size and apoptosis.…”
mentioning
confidence: 99%
“…The interleukin-1 (IL-1) system plays a significant role in the myocardial response to ischemia and infarct healing in a delicate balance between pro-and anti-inflammatory mediators [1][2][3][4][5][6][7][8][9][10]. Interleukin-1 receptor antagonist (IL-1Ra) is a naturally occurring antiinflammatory protein, member of the IL-1 family, released during AMI [6,[11][12][13][14]. We have recently shown that administration of the drug anakinra, a recombinant human IL-1 receptor antagonist, within 24 h of experimental AMI in an animal model significantly attenuates cardiac remodelling 7 days after AMI, mainly by inhibition of cardiomyocyte apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…We used relative change for the primary outcome to control for baseline biomarker levels as many of the investigational biomarkers included in this study have been associated with infarct size [15,17,18]. The primary outcome of interest was the 90-day composite of all-cause death, shock or heart failure (new or worsening).…”
Section: Discussionmentioning
confidence: 99%